A handbook for social science field research : essays & bibliographic sources on research design and methods - Curran, Sara R.; Perecman, Ellen (Sage Publications, 2006)
A Handbook for Social Science Field Research provides both novice and experienced researcher with valuable insights into a key list of critical texts pertaining to a wide array of social science methods useful when doing fieldwork. Through essays on everything from ethnography to case study, archival research, oral history, surveys, secondary data analysis and ethics, this refreshing new collection offers `tales from the field' by renowned scholars across various disciplines.